2015
DOI: 10.1093/aje/kwu325
|View full text |Cite
|
Sign up to set email alerts
|

Pooled Results From 5 Validation Studies of Dietary Self-Report Instruments Using Recovery Biomarkers for Potassium and Sodium Intake

Abstract: We pooled data from 5 large validation studies (1999-2009) of dietary self-report instruments that used recovery biomarkers as referents, to assess food frequency questionnaires (FFQs) and 24-hour recalls (24HRs). Here we report on total potassium and sodium intakes, their densities, and their ratio. Results were similar by sex but were heterogeneous across studies. For potassium, potassium density, sodium, sodium density, and sodium:potassium ratio, average correlation coefficients for the correlation of repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
253
4
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(280 citation statements)
references
References 36 publications
20
253
4
3
Order By: Relevance
“…Recent findings suggest that participants with higher BMI tended to underreport their calorie consumption. 39 It could also potentially relate to reverse causation in which heavier children sought to reduce their total calorie consumption. 40 Finally, despite the fact that we were limited in our ability to assess for changes in physical activity due to alterations in the assessment technique over the time period, data from the Youth Risk Behavior Surveillance system showed that there is increasing sedentary behaviors among US adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings suggest that participants with higher BMI tended to underreport their calorie consumption. 39 It could also potentially relate to reverse causation in which heavier children sought to reduce their total calorie consumption. 40 Finally, despite the fact that we were limited in our ability to assess for changes in physical activity due to alterations in the assessment technique over the time period, data from the Youth Risk Behavior Surveillance system showed that there is increasing sedentary behaviors among US adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Mean percentage differences between self-reported and biomarker intakes were estimated as 100 × exponential (mean of log self-reported -mean log biomarker value) -100 (27,28). In addition, nutrient intakes were energy-adjusted by using a density method: percentage of energy for protein and intake per 1000 kcal for potassium and sodium.…”
Section: Discussionmentioning
confidence: 99%
“…The 24-h dietary recall data used to estimate sodium intake are subject to reporting bias and exclude salt added at the table which could affect estimates of overall sodium intake (46). The USDA FNDDS do not include brand-specific manufacturer food codes for most foods.…”
Section: Discussionmentioning
confidence: 99%